Simulation Study of Turbulent Convective Heat Transfer Enhancement in Heated Tube Flow Using Tio2-Water Nanofluid - M. Hussein, Adnan; R. A., Bakar; K., Kadirgama; Sharma, K. V. (IOP Publishing, 2013)
Simulation by convenient software same as FLUENT was used to predict the friction factor and Nusselt number for forced convection heat transfer of TiO2-water nanofluid. The range of Reynolds number is from 10000 to 100000 to be turbulent flow in a horizontal straight tube with heat flux 5000 w/m2 around it. The volume fraction of nanoparticle was (0.25%, 0.5%, 0.75% and 1%) and diameter of particle is 27nm. The results show that the friction factor and Nusselt number are increasing with increasing of volume fraction. Results compared with the experimental data available in literature and there are good agreements